2020
DOI: 10.1183/13993003.03104-2020
|View full text |Cite
|
Sign up to set email alerts
|

Free-breathing MRI for monitoring ventilation changes following antibiotic treatment of pulmonary exacerbations in paediatric cystic fibrosis

Abstract: It is published here in its accepted form prior to copyediting and typesetting by our production team. After these production processes are complete and the authors have approved the resulting proofs, the article will move to the latest issue of the ERJ online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 17 publications
1
26
1
Order By: Relevance
“…However, in the Kaireit et al study a threshold of 90th percentile × 0.4 was used to determine VDP from RVent distributions, whereas a k-means clustering was used in the present study to stay consistent with previous work in pediatric CF. 11,26,28 VDP parameters derived from PREFUL MRI showed high intravisit repeatability, comparable to VDP Xe-MS and VDP Xe-SS in the pediatric CF group; however, factors affecting the variability of the two methods differ. Variability in Xe-MRI ventilation distributions could be attributed to the differences in the breath-hold performed by the patient (i.e., more or less the gas volume inhaled relative to the prescribed dose), whereas for PREFUL MRI previous studies have shown that changes in breathing frequency and tidal volumes can influence RVent values.…”
Section: Discussionmentioning
confidence: 80%
“…However, in the Kaireit et al study a threshold of 90th percentile × 0.4 was used to determine VDP from RVent distributions, whereas a k-means clustering was used in the present study to stay consistent with previous work in pediatric CF. 11,26,28 VDP parameters derived from PREFUL MRI showed high intravisit repeatability, comparable to VDP Xe-MS and VDP Xe-SS in the pediatric CF group; however, factors affecting the variability of the two methods differ. Variability in Xe-MRI ventilation distributions could be attributed to the differences in the breath-hold performed by the patient (i.e., more or less the gas volume inhaled relative to the prescribed dose), whereas for PREFUL MRI previous studies have shown that changes in breathing frequency and tidal volumes can influence RVent values.…”
Section: Discussionmentioning
confidence: 80%
“…A previous study has also indicated the ventilation defect calculated with PREFUL correlates with ventilation defect measured with HP 129 Xe in children with CF 24 . There is also recent work demonstrating the detection of antibiotic treatment‐related improvements in ventilation with PREFUL, similar to HP 129 Xe in pediatric CF 32 . Therefore, PREFUL MRI holds promise for future neonatal and infant functional lung imaging.…”
Section: Discussionmentioning
confidence: 91%
“…24 There is also recent work demonstrating the detection of antibiotic treatment-related improvements in ventilation with PREFUL, similar to HP 129 Xe in pediatric CF. 32 Therefore, PREFUL MRI holds promise for future neonatal and infant functional lung imaging. The low barrier to PREFUL implementation, requiring only standard scanner hardware and common GRE pulse sequences makes PREFUL MRI more readily adaptable for evaluation in infants without the need for exogenous contrast or dedicated infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Fourier decomposition (FD) MRI and derivations such as Phase-Resolved FUnctional Lung (PREFUL) MRI sequences, both ventilation and perfusion can be assessed without intravenous or gaseous inhaled contrast administration ( 96 ). PREFUL MRI is also feasible in uncooperative patients, since it is performed in free-breathing conditions ( Figure 10 ).…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…Moreover, PREFUL-MRI does not use gadolinium, the use of which is debated because of concerns regarding potential tissue deposition ( 97 ). Munisada et al demonstrated that, during RTE, the ventilation distribution obtained with FD is correlated with hyperpolarized gas imaging and both can monitor functional improvement after therapy ( 96 ).…”
Section: Imaging Techniquesmentioning
confidence: 99%